Observe the following statements I: The circle x2+y2-6x-4y-7=0 touch y-axis

1.  both I and II are true

2.  neither I nor lI true

3.  I is true, II is false

4.  I is false, II is true

4

neither I nor lI true

Explanation :
No Explanation available for this question

If a, b, c are the radii of the circle x2+y2-6x-8y=0, x2+y2+4x-6y-3=0, x2+y2+6x+4y-11=0 then the ascending order of a,b,c is

1.  a, b, c

2.  b, c, a

3.  a, c, b

4.  b, a, c

4

b, a, c

Explanation :
No Explanation available for this question

If the of the circle passing through the points (3,4),(3,2),(1,4) is x2+y2+2ax+2by+c=0, then the ascending order of a, b, c is

1.  a, b, c

2.  b, c, a

3.  a, c, b

4.  b, a, c

4

b, a, c

Explanation :
No Explanation available for this question

If a, b, c are the lengths of tangents from (0, 0) to the circle x2+y2-3x-4y+1=0, x2+y2+4x-6y+4=0, x2+y2-6x-12y+9=0 then the ascending order of a, b, c is

1.  a, b, c

2.  b, c, a

3.  a, c, b

4.  b, a, c

4

a, b, c

Explanation :
No Explanation available for this question

If P1, P2, P3, are the perimeters of the circle x2+y2+8x-6y=0, 4x2+4y2-4x-12y-186=0 and x2+y2-6x+6y-9=0 respectively, then

1.  P1

2.  P1

3.  P3

4.  P2

4

P1<P3<P2

Explanation :
No Explanation available for this question

If 13 sin A=12, π/2 < A < π and sec B =5, 3π/2 < B < 2π then 5 tan A+3 tan2 B=

1.  20/3

2.  -20/3

3.   22/3

4.  -22/3

4

-20/3

Explanation :
No Explanation available for this question

3[sin4(3π/2-α)+ sin4(3π+α)]-2[sin6(π/2+α)+ sin6(5π-α)]=

1.  0

2.  1

3.  3

4.  sin 4 α+ cos 6 α

4

1

Explanation :
No Explanation available for this question

(sin θ+ cosec θ)2+(cos θ+ sec θ)2 =

1.  tan2 θ+ cot2 θ+7

2.  sin2 θ+ cos2 θ+7

3.  sec2 θ+ cosec2 θ+7

4.  cos2 θ+ cot2 θ+7

4

tan2 θ+ cot2 θ+7

Explanation :
No Explanation available for this question

(cos θ+ sin θ)2+(cos θ- sin θ)2 =

1.  0

2.  1

3.  2

4.  √2

4

2

Explanation :
No Explanation available for this question

(tan α+ cosec β)2-(cot β- sec α)2 =

1.  2tan α cot β(cosec α+ sec β)

2.  2sec α cosec β(cot α+ tan β)

3.  2cot αtan β(sec α+ cosec β)

4.  2cosec α sec β(tan α+ cot β)

4